ARTIFICIAL INTELLIGENCE AND BIG DATA IN MANAGEMENT CONTROL OF MOROCCAN COMPANIES: CASE OF THE RABAT-SALE-KENITRA REGION - Gaga Dounia; Hilmi Yassine; Benarbi Houda; Kaizar Chaimae (Proceedings on Engineering Sciences)
Technological advancements, particularly Big Data and Artificial Intelligence (AI), are profoundly transforming management practices and redefining the roles of management controllers. These technologies have become essential tools, requiring mandatory adoption to optimize organizational performance. This research aims to analyze the impact of integrating Big Data and AI on management control and organizational performance, questioning how these technologies influence these areas. AA qualitative study, combining a literature review with interviews with management controllers, administrative and financial managers, and general directors, was conducted. The results reveal that the integration of Big Data and AI represents both an opportunity and a threat for management controllers. They must adopt a proactive stance to maintain their role within the organization. These technologies cause significant disruptions in management control, altering the roles and responsibilities of controllers. Professionals anticipate that their future tasks will be influenced by these technologies and view their evolution towards business partner roles favorably, adding value through advisory tasks. This transformation is seen as a means to enhance organizational performance by optimizing decision-making and operational processes.© 2024 Published by Faculty of Engineering.